Effect of Activated Carbon Addition on the Burning Rate and Energetic Characteristics of Sodium Nitrate–Sucrose Composite Solid Propellants - Aura Restu Sabila; Anceu Murniati (Indonesian Journal of Chemical Studies, 2026)
Composite solid propellants are widely used in rocket propulsion and gas-generating systems; however, many conventional formulations rely on chlorine-containing oxidizers that raise environmental concerns. This study evaluates a sodium nitrate–sucrose composite solid propellant and investigates the effect of activated carbon addition on combustion behavior and energetic characteristics. The propellant system consists of sodium nitrate as the oxidizer, sucrose as the fuel, unsaturated polyester resin as the binder, and activated carbon as a combustion-modifying additive. Two formulations, with and without activated carbon, were prepared to assess the influence of activated carbon on the composite system. The samples were characterized using visual inspection, linear burning-rate testing (n = 5), calorific value measurement by bomb calorimetry, Fourier Transform Infrared (FTIR) spectroscopy, and statistical analysis using Welch’s t-test (α = 0.05). The formulation containing activated carbon exhibited a more controlled burning rate and showed a statistically significant difference compared with the formulation without activated carbon. The calorific value increased from 3338 - 4111 cal g⁻¹, equivalent to 13.908 – 17.129 kJ g⁻¹, while the calculated reaction enthalpy (−968 cal g⁻¹) confirmed the exothermic nature of the base sodium nitrate–sucrose system. FTIR analysis indicated the presence of characteristic functional groups and suggested possible interactions within the composite matrix, particularly involving oxygen-containing groups and activated carbon. These results indicate that activated carbon functions as a combustion-modifying additive that influences both burning rate and energetic characteristics. The findings represent a preliminary laboratory-scale evaluation of formulation effects in sodium nitrate–sucrose composite solid propellants.